Severe acute pancreatitis caused by adhesive intestinal obstruction following fundoplication - Yuka Ooe; Seisho Sakai; Jun Kinoshita; Isamu Makino; Keishi Nakamura; Tomoharu Miyashita; Hidehiro Tajima; Hiroyuki Takamura; Itasu Ninomiya; Sachio Fushida; Tetsuo Ohta (Elsevier, 2020)
Background: Our patient was a 21-year-old man with cerebral palsy and a history of laparoscopic fundoplication for hiatal hernia at the age of 11 years and gastrostomy at the age of 18 years. Case presentation: The patient was referred to our department when his hematological examination revealed fever caused by an inflammatory response, and elevated amylase levels. Computed tomography examination revealed adhesions around the gastrostomy and dilation from the stomach to the upper jejunum. In addition, a wide range of adipose tissue intensity was seen around the pancreas, and he was diagnosed with adhesive intestinal obstruction and severe acute pancreatitis. Conservative treatment of the adhesive intestinal obstruction was performed. For the pancreatitis, we administered antibiotics and protease inhibitors, continuous hemodiafiltration, and intra-arterial therapy, and the patient's condition improved. On hospital day 24, we performed adhesiotomy to treat the adhesive intestinal obstruction. The patient's postoperative course was favorable, and he was transferred on hospital day 41. Conclusions: Acute pancreatitis accompanying afferent loop obstruction has been reported after gastrectomy. In our patient, gas bloat syndrome and adhesive intestinal obstruction caused by fundoplication resulted in increased intestinal pressure, and it appeared that pancreatitis developed by a similar mechanism. In this report, we discuss our experience with this patient and a review of the literature.